Zero- to low-field relaxometry of chemical and biological fluids - Seyma Alcicek; Piotr Put; Adam Kubrak; Fatih Celal Alcicek; Danila Barskiy; Stefan Gloeggler; Jakub Dybas; Szymon Pustelny (Communications Chemistry, 2023)
Abstract Nuclear magnetic resonance (NMR) relaxometry is an analytical method that provides information about molecular environments, even for NMR “silent” molecules (spin-0), by analyzing the properties of NMR signals versus the magnitude of the longitudinal field. Conventionally, this technique is performed at fields much higher than Earth’s magnetic field, but our work focuses on NMR relaxometry at zero and ultra-low magnetic fields (ZULFs). Operating under such conditions allows us to investigate slow (bio)chemical processes occurring on a timescale from milliseconds to seconds, which coincide with spin evolution. ZULFs also minimize T 2 line broadening in heterogeneous samples resulting from magnetic susceptibility. Here, we use ZULF NMR relaxometry to analyze (bio)chemical compounds containing 1H-13C, 1H-15N, and 1H-31P spin pairs. We also detected high-quality ULF NMR spectra of human whole-blood at 0.8 μT, despite a shortening of spin relaxation by blood proteomes (e.g., hemoglobin). Information on proton relaxation times of blood, a potential early biomarker of inflammation, can be acquired in under a minute using inexpensive, portable/small-size NMR spectrometers based on atomic magnetometers.